When HERG-caused LQT2 encounters antisense oligonucleotide: is exon 6 skipping therapy plausible? - Zheng, Zequn; Song, Yongfei (Frontiers in Pharmacology, 2025)
Graphical AbstractThe unique in‐frame exon 6 of the HERG gene as a potential target for antisense oligonucleotide‐mediated exon skipping therapy.